Opinion dynamics in finance and business: A literature review and research opportunities - Quanbo Zha; Gang Kou; Hengjie Zhang; Haiming Liang; Xia Chen; Cong-Cong Li; Yucheng Dong (Financial Innovation, 2020)
Opinion dynamics is an opinion evolution process of a group of agents, where the final opinion distribution tends to three stable states: consensus, polarization, and fragmentation. At present, the opinion dynamics models have been extensively studied in differrent fields. This paper provides a review of opinion dynamics in finance and business, such as, finance, marketing, e-commerce, politics, and group decision making. Furthermore, identified research challenges have been proposed to promote the future research of this topic.
Keywords: 650; Business; Financial market; Opinion dynamics; Opinion dynamics; Financial market; Business